Determinants of teacher’s behavioural intention to use social networking sites / Hasbullah Idris - Hasbullah, Idris (2017)
Social Networking Sites are the web-based applications that enables the distribution, dissemination and retrieval of information via both online and offline mode of communications. The robust features of Social Networking Sites had been widely used by all communities including teachers. There are many studies in social networking sites to be associated with student's behaviour including schools and university students but little study has been made for the school teachers especially in examining the teacher's behaviour towards Social Networking Sites (SNSs). Therefore, the objectives of the study were (i) to examine the mean differences in teacher’s behavioral intention to use SNS between male and female teachers, (ii) to examine the mean differences in teacher’s behavioural intention to use SNS between age group and (iii) to investigate factors that influence teacher’s behavioural intention to use SNS. The data was collected by using a survey questionnaire to 133 teachers at 8 fully residential schools at one of the southern states in Malaysia. All of the data collected were analysed by using SPSS (Statistical Product Services and Solutions) version 23. The Spearman’s Rho and Mann Whitney U-test were the inferential tests to be used as to test the relationship and the mean rank between the variables of the study. The results revealed that all of the variables in uses and gratifications and social influences were found to be correlated with the teacher's behavioural intention to use Social Networking Sites (SNSs). Among the significant of the study was to provide empirical evidence as some indicators to the authorities especially to the policy makers that teachers are ready to face the challenges of the 21st century learning.